The kringle IV type 2 domain variant 4925G>A causes the elusive association signal of the LPA pentanucleotide repeat - Rebecca Grüneis; Hansi Weissensteiner; Claudia Lamina; Sebastian Schönherr; Lukas Forer; Silvia Di Maio; Gertraud Streiter; Annette Peters; Christian Gieger; Florian Kronenberg; Stefan Coassin (Journal of Lipid Research, 2022)
Lipoprotein(a) [Lp(a)] concentrations are regulated by the LPA gene mainly via the large kringle IV-type 2 (KIV-2) copy number variation and multiple causal variants. Early studies suggested an effect of long pentanucleotide repeat (PNR) alleles (10 and 11 repeats, PNR10 and PNR11) in the LPA promoter on gene transcription and found an association with lower Lp(a). Subsequent in vitro studies showed no effects on mRNA transcription, but the association with strongly decreased Lp(a) remained consistent. We investigated the isolated and combined effect of PNR10, PNR11, and the frequent splice site variant KIV-2 4925G>A on Lp(a) concentrations in the Cooperative Health Research in the Region of Augsburg F4 study by multiple quantile regression in single-SNP and joint models. Data on Lp(a), apolipoprotein(a) Western blot isoforms, and variant genotypes were available for 2,858 individuals. We found a considerable linkage disequilibrium between KIV-2 4925G>A and the alleles PNR10 and PNR11. In single-variant analysis adjusted for age, sex, and the shorter apo(a) isoform, we determined that both PNR alleles were associated with a highly significant Lp(a) decrease (PNR10: β = −14.43 mg/dl, 95% CI: −15.84, −13.02, P = 3.33e-84; PNR11: β = −17.21 mg/dl, 95% CI: −20.19, −14.23, P = 4.01e-29). However, a joint model, adjusting the PNR alleles additionally for 4925G>A, abolished the effect on Lp(a) (PNR10: β = +0.44 mg/dl, 95% CI: −1.73, 2.60, P = 0.69; PNR11: β = −1.52 mg/dl, 95% CI: −6.05, 3.00, P = 0.51). Collectively, we conclude that the previously reported Lp(a) decrease observed in pentanucleotide alleles PNR10 or PNR11 carriers results from a linkage disequilibrium with the frequent splicing mutation KIV-2 4925G>A.